Endoplasmic Reticulum stress reduces COPII vesicle formation and modifies Sec23a cycling at ERESs. Issue 19 (27th August 2013) - Amodio, Giuseppina; Venditti, Rossella; De Matteis, Maria Antonietta; Moltedo, Ornella; Pignataro, Piero; Remondelli, Paolo
Abstract : Exit from the Endoplasmic Reticulum (ER) of newly synthesized proteins is mediated by COPII vesicles that bud from the ER at the ER Exit Sites (ERESs). Disruption of ER homeostasis causes accumulation of unfolded and misfolded proteins in the ER. This condition is referred to as ER stress. Previously, we demonstrated that ER stress rapidly impairs the formation of COPII vesicles. Here, we show that membrane association of COPII components, and in particular of Sec23a, is impaired by ER stress‐inducing agents suggesting the existence of a dynamic interplay between protein folding and COPII assembly at the ER. Abstract : ER stress reduces the amount of membrane bound Sec23a. GFP‐Sec23a cycles more rapidly at ERES of ER stressed cells. ER stress induces faster Sec23a release from COPII vesicles. ER stress reduced the amount of vesicle bound Sec31a.